Relationship Between Climate Change and International Investment Law. Lack of Precision in BITs and its Impact on Further Dispute Settlements. - Rahimli, Ayana (My University, 2026)
The interaction between Climate Change and International Investment Law is considered a crucial study due to the rising periodicity and complexity of disputes where environmental protection and investor rights interfere. The lack of precision in Bilateral Investment Treaties (BITs) covering environmental provisions and sustainable development objectives specifically gives rise to this issue. This uncertainty created by the legal gap causes arbitral tribunals to act in the restricted guidance on how to set the impartiality between investor protection in compliance with the host state’s regulations as an obligation under International Environmental Law and Multilateral Climate Agreements, such as the Paris Agreement. There is an urge in harmonized treaty languages concerning climate change. This study explores the climate change legislation in the first chapter. In the second chapter of the thesis, aspects such as dispute settlement according to BITs, and related to the topic, BIT provisions, are covered broadly. Besides the legal research, this study includes the analysis of two different cases, those are discussed in the last chapter. Finally, this study concludes by recommending the alignment of BITs with climate goals.
Keywords: Climatic changes -- Law and legislation.; Environmental law; International.; Investments; Foreign (International law).; Sustainable development -- Law and legislation.